Effects of a Single Universal Extra Dimension in Bc→Ds,Dl+l- Decays - U. O. Yilmaz; E. Danapinar (Advances in High Energy Physics)
The rare semileptonic Bc→Ds,dl+l- decays are studied in the universal extra dimension with a single extra dimension scenario. The sensitivity of differential and total branching ratios and polarization asymmetries of final state leptons to the compactification parameter are presented, for both muon and tau decay channels. Considering the ability of available experiments, it would be useful to study these effects.